2016
DOI: 10.1111/jocn.13358
|View full text |Cite
|
Sign up to set email alerts
|

Challenging graduate nurses' transition: Care of the deteriorating patient

Abstract: The findings identify needs of graduate nurses' during a high-stakes patient encounter and shed light upon one aspect of transition. Clinical leaders may use the findings from this study to improve preceptor development and transition programme curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…However, the amount and quality of sleep, depression and stress were worse at 6 weeks and then slightly improved after 6 months, which was still worse than at baseline. These experiences of novice nurses have been frequently reported in literature from other cultures (Bisholt, 2012;Della Ratta, 2016;Ketelaar et al, 2015;Nahm, Warren, Zhu, An, & Brown, 2012;O'Shea & Kelly, 2007). In addition to lacking the nursing knowledge and skills necessary for the multidimensional responsibility in clinical settings, novice nurses reportedly experience a lack of knowledge about and accessibility to health promotion strategies.…”
Section: Discussionmentioning
confidence: 77%
“…However, the amount and quality of sleep, depression and stress were worse at 6 weeks and then slightly improved after 6 months, which was still worse than at baseline. These experiences of novice nurses have been frequently reported in literature from other cultures (Bisholt, 2012;Della Ratta, 2016;Ketelaar et al, 2015;Nahm, Warren, Zhu, An, & Brown, 2012;O'Shea & Kelly, 2007). In addition to lacking the nursing knowledge and skills necessary for the multidimensional responsibility in clinical settings, novice nurses reportedly experience a lack of knowledge about and accessibility to health promotion strategies.…”
Section: Discussionmentioning
confidence: 77%
“…Debriefing sessions were also described by preceptors as essential to vent emotions arising from the event and to offer reassurance to novices. Novice nurses’ need for emotional support following emergency response situations has been previously noted (Della Ratta, ; Ranse & Arbon, ). The participants in the current study understood the impact that caring for a critically ill patient may have on new graduate role formation as they used debriefing sessions to reassure novices.…”
Section: Discussionmentioning
confidence: 87%
“…As a result, the ability to verbalise an accurate assessment and plan of the patient upon reflection was viewed by the preceptors as a more important indicator of clinical judgement development. Explicitly stating this to novices may provide reassurance as previous research focusing on deteriorating patient encounters from the novice perspective revealed that “success or failure” of their performance during the encounter was highly regarded as a measure of their own professional development and impacted transition (Della Ratta, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations